#### Answer

It is necessary to reflect $f(x)$ about the y-axis and then, move the new graph 3 units to the right.

#### Work Step by Step

Observe:
$f(0)=10^0=1$ which gives the point: $(0,1)$
$g(3)=10^{-3+3}=10^0=1$ which gives the point: $(3,1)$
$f(1)=10^1=10$ which gives the point: $(1,10)$
$g(2)=10^{-2+3}=10^1=10$ which gives the point: $(2,10)$
$f(2)=10^2=100$ which gives the point: $(2,100)$
$g(1)=10^{-2+3}=10^2=100$ which gives the point: $(1,100)$
That is, $f(x)$ and $g(x)$ increase in opposite directions. In order to obtain $g(x)$ it is necessary to reflect $f(x)$ about the y-axis and then, move the new graph 3 units to the right.